The Basics of Fertilizing Pasture - Martha Thomas; Maria Silveira (EDIS, 2009)
Revised! SL269, a 3-page fact sheet by Martha Thomas and Maria Silveira, outlines the basics of pasture fertilization for grazing, seed harvesting, or hay production. Published by the UF Department of Soil and Water Science, October 2008. Revised November 2008.